2017
DOI: 10.21474/ijar01/3738
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude of Medical Fraternity Towards Whole Body and Organ Donation

Abstract: This study is undertaken to evaluate the awareness and attitude of medical fraternity towards whole body and organ donation. A cross sectional study was conducted among undergraduates, graduates and post graduates. Total 500 participants answered the multiple choice questionnaire containing information about demographic features, awareness and attitude towards whole body and organ donation. Out of 500 participants, 44% were willing to donate organs, 47.8% were willing to donate body only for organ transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Both global and Indian trends show an overall positive attitude among students, but there are some exceptions. Prameela et al, in their study, showed that only 6% of students were willing to donate their bodies for dissection [ 41 ] as opposed to 48% of students who showed a willingness toward organ donation. Though there is an overall positive attitude toward VBD, when opinion about donation is categorized into self, by a stranger, or a family member, the study by Mwachaka et al revealed that 68.1% [ 39 ] were opposed to self-body donation and 59.2% recommended donation by strangers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both global and Indian trends show an overall positive attitude among students, but there are some exceptions. Prameela et al, in their study, showed that only 6% of students were willing to donate their bodies for dissection [ 41 ] as opposed to 48% of students who showed a willingness toward organ donation. Though there is an overall positive attitude toward VBD, when opinion about donation is categorized into self, by a stranger, or a family member, the study by Mwachaka et al revealed that 68.1% [ 39 ] were opposed to self-body donation and 59.2% recommended donation by strangers.…”
Section: Discussionmentioning
confidence: 99%
“…Prameela et al identified self-motivation as one of the significant facilitators. In their study, 55.4% of the donors admitted that the motivation for donating their bodies was self-driven [ 41 ]. In contrast, Ciliberti et al, in their study, found an altruistic attitude of participants toward VBD [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations